In-vitro Antioxidant and Alpha-Glucosidase Inhibitory Activities of Ethanolic Extracts of Aerial Part Extracts of Gymnema sylvestre - Ibrahim, Abdullahi; S.L. Muhammad; Yahaya Yakubu; Jafar Yusu; Ahmad Muhammad Sani (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2025)
Gymnema sylvestre is a medicinal woody climber that has been used in ethnomedicine for the treatment of stomach ailments, constipation, liver diseases. Similarly employed in the treatment of hypertension, tachycardia, diabetes and oxidative stress. This work investigated the antioxidant and α-glucosidase inhibitory activity of G. sylvestre aerial part extracts. Ethanol was used to macerate the powdered aerial portion, and the resulting crude extract was then separated into several fractions. Evaluation of the fractions for α-glucosidase inhibition and antioxidant activity was conducted using 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and α-glucosidase by spectrophotometer. The ethanol and chloroform fractions demonstrate α-glucosidase inhibition with IC50 values of 618.7± 27μg/ml and 37.73± 0.38. μg/ml, respectively, and an IC50 value of 20.07 ± 19.75µg/ml and 91.65 ± 32.97µg/ml. In contrast, the aqueous and ethyl acetate fractions showed considerable α-glucosidase inhibition, with respective IC50 values of 116.47± 13.65 µg/ml and 97.46± 16.09 µg/ml. Based on the findings, it was proposed that the aerial portion of Gymnema sylvestre might contain substances with mild α-glucosidase inhibitory effects.